Early double-negative thymocyte export in Trypanosoma cruzi infection is restricted by sphingosine receptors and associated with human chagas disease. - Ailin Lepletier; Liliane de Almeida; Leonardo Santos; Luzia da Silva Sampaio; Bruno Paredes; Florencia Belén González; Célio Geraldo Freire-; Juan Beloscar; Oscar Bottasso; Marcelo Einicker-Lamas; Ana Rosa Pérez; Wilson Savino; et al. (Public Library of Science (PLoS), 2014)
The protozoan parasite Trypanosoma cruzi is able to target the thymus and induce alterations of the thymic microenvironmental and lymphoid compartments. Acute infection results in severe atrophy of the organ and early release of immature thymocytes into the periphery. To date, the pathophysiological effects of thymic changes promoted by parasite-inducing premature release of thymocytes to the periphery has remained elusive. Herein, we show that sphingosine-1-phosphate (S1P), a potent mediator of T cell chemotaxis, plays a role in the exit of immature double-negative thymocytes in experimental Chagas disease. In thymuses from T. cruzi-infected mice we detected reduced transcription of the S1P kinase 1 and 2 genes related to S1P biosynthesis, together with increased transcription of the SGPL1 sphingosine-1-lyase gene, whose product inactivates S1P. These changes were associated with reduced intrathymic levels of S1P kinase activity. Interestingly, double-negative thymocytes from infected animals expressed high levels of the S1P receptor during infection, and migrated to lower levels of S1P. Moreover, during T. cruzi infection, this thymocyte subset expresses high levels of IL-17 and TNF-α cytokines upon polyclonal stimulation. In vivo treatment with the S1P receptor antagonist FTY720 resulted in recovery the numbers of double-negative thymocytes in infected thymuses to physiological levels. Finally, we showed increased numbers of double-negative T cells in the peripheral blood in severe cardiac forms of human Chagas disease.